2019
DOI: 10.4103/jmas.jmas_217_17
|View full text |Cite
|
Sign up to set email alerts
|

Changes of serum and peritoneal inflammatory mediators in laparoscopic radical resection for right colon carcinoma

Abstract: Laparoscopic surgery for the treatment of right colon carcinoma has the advantages of fewer traumas, less systemic and local inflammatory response, rapider post-operative recovery and shorter hospital stay. It is worthy of clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Several studies have suggested that the crosstalk between cancer cells and host’s stromal cells may participate in the establishment of a permissive tumoral environment that subsequently favors residual disease growth and chemoresistance [ 5 11 ]. However, only few studies have provided a global approach, considering the macro-environmental changes associated with surgery [ 12 14 ]. Beyond cell–cell interactions, peritoneal trauma induced by surgery may also participate in the constitution of a niche for residual cancer cells through overproduction of secreted factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that the crosstalk between cancer cells and host’s stromal cells may participate in the establishment of a permissive tumoral environment that subsequently favors residual disease growth and chemoresistance [ 5 11 ]. However, only few studies have provided a global approach, considering the macro-environmental changes associated with surgery [ 12 14 ]. Beyond cell–cell interactions, peritoneal trauma induced by surgery may also participate in the constitution of a niche for residual cancer cells through overproduction of secreted factors.…”
Section: Introductionmentioning
confidence: 99%